Humanities beyond the Classroom: Blessed Be the Human Ties That Bind - Richards, David (Maine Policy Review, 2015)
David Richards describes his experiences with public humanities programs in Maine. Since 1998 he has facilitated nearly 100 book series and led over 400 discussions. Most of these events have been offered through two programs of the Maine Humanities Council’s Harriet P. Henry Center for the Book: New Books, New Readers and Let’s Talk About It.
Keywords: public humanities; facilitated discussion; Maine